Intellectual disability is associated with increased risk for obesity in a nationally representative sample of U.S. children. Issue 3 (July 2016) - Segal, Mary; Eliasziw, Misha; Phillips, Sarah; Bandini, Linda; Curtin, Carol; Kral, Tanja V.E.; Sherwood, Nancy E.; Sikich, Lin; Stanish, Heidi; Must, Aviva
Abstract: Background: Data on obesity prevalence in children with intellectual disability (ID) are scarce. Objective: We estimated rates of obesity among children aged 10–17 years with and without ID in a nationally representative dataset that included measures of child weight and ID status, as well as family meal frequency, physical activity, and sedentary behavior. Methods: Chi-square tests compared prevalence of obesity, demographic and behavioral characteristics between children with and without ID as reported in the 2011 National Survey of Children's Health. Tests for interaction in logistic regression models determined whether associations between obesity and behavioral characteristics were different between children with/without ID. Results: Obesity prevalence for children with ID was 28.9% and 15.5% for children without ID. After adjusting for age, sex, race/ethnicity and poverty level, the odds ratio was significantly 1.89 times greater among children with ID than among those without ID (95% CI: 1.14 to 3.12). Among children with ID, 49.8% ate at least one meal with family members every day compared to 35.0% without ID ( p < 0.002), and 49.5% with ID participated in frequent physical activity compared to 62.9% ( p < 0.005). Prevalence of obesity was higher among all children who ate family meals every day compared to fewer days per week, and the effect was significantly more pronounced among those with ID ( p = 0.05). Conclusions: Prevalence of obesity among youth with ID was almost double that of the general population. Prospective studies are needed in this population to examine the impact of consistent family mealtimes and infrequent physical activity.